CURRENT AND DESIRABLE CONDITIONS AND NEEDS FOR DEVELOPING ACADEMIC MANAGEMENT OF ISLAMIC PRIVATE SCHOOLS IN THAILAND BASED ON THE CONCEPT OF MUSLIM YOUTH CHARACTERISTICS FOR FUTURE GLOBAL SOCIETY - อัซซอมาดีย์, มูฮำหมัด; Xupravati, Penvara; Chaemchoy, Sukanya (Al-HIKMAH Journal, 2024)
This study was descriptive research. The objective of this research were to study the current and desirable conditions and needs for developing Academic Management of Islamic Private Schools in Thailand based on the concept of Muslim Youth Characteristics for Future Global Society. The sample group was 111 Islamic Private Schools in Thailand. Data were collected using questionnaires. The data were analyzed by finding percentage, mean, standard deviation, and PNImodified The results of the research found that, 1) The current conditions of curriculum development has the highest average ( = 4.185), followed by teaching and learning ( = 4.173) and measurement and evaluation ( = 4.094), respectively. Desirable conditions teaching and learning management has the highest average ( = 4.746), followed by curriculum development ( = 4.730) and measurement and evaluation ( = 4.687), respectively, and the necessary need value is measurement and evaluation. It has the highest order of essential needs (PNImodified = 0.145), followed by teaching and learning management (PNImodified = 0.137) and curriculum development (PNImodified = 0.130), respectively. 2) The current state of characteristics of Muslim youth for the future world society Aspects of Islamic faith and practice has the highest average ( = 4.269) and thinking has the lowest average ( = 4.084), a desirable condition Aspects of Islamic faith and practice has the highest average ( = 4.764) and adaptability has the lowest average ( = 4.690) and the highest need is the thinking aspect It has the highest order of essential needs (PNImodified = 0.158) and Islamic faith and practice. Has the lowest order of essential needs (PNImodified = 0.116)